(untitled) (Victoria Journal of Management, 2025)
Ethical business practices are pivotal in fostering employee retention by creating a positive work environment that nurtures trust, satisfaction, and loyalty among employees. Employee loyalty serves as a critical mediator, strengthening the connection between ethical business practices and retention by enhancing employees’ commitment to staying with organizations they trust and respect. This study examines the role of employee loyalty in mediating the relationship between ethical business practices and employee retention within Nepal’s hospitality sector, specifically focusing on restaurants and cafes. Data were gathered from 392 respondents through a structured questionnaire distributed using a convenience sampling method. The sample comprised support staff, assistant-level employees, and managerial personnel from various restaurants and cafes in the Kathmandu Valley. The data analysis was performed using Process Macro 4 with a 95% confidence interval and 5,000 bootstrapping samples. The results indicate that employee loyalty acts as a full mediator in the relationship between ethical business practices and employee retention. This study highlights the critical role of ethical business practices in cultivating trust and credibility with stakeholders, driving organizational success, and reducing employee turnover. By prioritizing ethical practices, organizations can strengthen employee loyalty, which significantly enhances retention rates and contributes to a more stable and committed workforce.